Long-term Outcomes of Additional Endoscopic Treatments for Patients with Positive Lateral Margins after Endoscopic Submucosal Dissection for Early Gastric Cancer - Tae-Se Kim; Byung-Hoon Min; Yang Won Min; Hyuk Lee; Poong-Lyul Rhee; Jae J. Kim; Jun Haeng Lee (Gut and Liver, 2022)
Background/Aims: It is uncertain whether additional endoscopic treatment may be chosen over surgery in patients with positive lateral margins (pLMs) as the only non-curative factor after endoscopic submucosal dissection (ESD) for early gastric cancer (EGC). We aimed to compare the long-term outcomes of additional endoscopic treatments in such patients with those of surgery and elucidate the clinicopathological factors that could influence the treatment selection. Methods: A total of 99 patients with 101 EGC lesions undergoing additional treatment after noncurative ESD with pLMs as the only non-curative factor were analyzed. Among them, 25 (27 lesions) underwent ESD, 29 (29 lesions) underwent argon plasma coagulation (APC), and 45 (45 lesions) underwent surgery. Clinicopathological characteristics and long-term outcomes were compared. Results: Residual tumor was found in 73.6% of cases. The presence of multiple pLMs was associated with higher risk of residual tumor (p=0.046). During a median follow-up of 58.9 months, recurrent or residual lesions after additional ESD and APC were found in 4% (1/25) and 6.8% (2/29) of patients, respectively. However, all were completely cured with surgery or repeated ESD. There were no extragastric recurrences after additional endoscopic treatment. Lymph node metastasis was identified after additional surgery in one (2.2%) patient with an EGC showing histological heterogeneity. Conclusions: Given the favorable long-term outcomes, additional ESD or APC may be an acceptable choice for patients with pLMs as the only non-curative factor after ESD for EGC. However, clincopathological characteristics such as multiple pLMs and histological heterogeneity should be considered in the treatment selection.